2011
DOI: 10.1083/jcb.201103129
|View full text |Cite
|
Sign up to set email alerts
|

Flo11p, drug efflux pumps, and the extracellular matrix cooperate to form biofilm yeast colonies

Abstract: Biofilm yeast colonies are complex structures that form through cooperative action of constituent cells and provide a protective environment for cell growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
118
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(127 citation statements)
references
References 47 publications
8
118
1
Order By: Relevance
“…Although most laboratory strains produce relatively unstructured "smooth" colonies, some natural isolates of S. cerevisiae produce colonies with complex multicellular features, such as folds, crevices, and channels that form as the colony grows on solid media (20,21). These "fluffy" colonies possess properties similar to those of microbial biofilms, including the secretion and maintenance of an extracellular matrix (21)(22)(23), localized expression of drug efflux pumps (23), increased adherence (24), and the use of cell-cell communication (25). Fluffy colony formation requires the function and coordination of numerous pathways that underlie the trait, and the deletion of key factors produces a smooth colony phenotype (26)(27)(28).…”
mentioning
confidence: 99%
“…Although most laboratory strains produce relatively unstructured "smooth" colonies, some natural isolates of S. cerevisiae produce colonies with complex multicellular features, such as folds, crevices, and channels that form as the colony grows on solid media (20,21). These "fluffy" colonies possess properties similar to those of microbial biofilms, including the secretion and maintenance of an extracellular matrix (21)(22)(23), localized expression of drug efflux pumps (23), increased adherence (24), and the use of cell-cell communication (25). Fluffy colony formation requires the function and coordination of numerous pathways that underlie the trait, and the deletion of key factors produces a smooth colony phenotype (26)(27)(28).…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that the budding yeast Saccharomyces forms microbial communities that have these biofilm characteristics (Kuthan et al 2003;Váchová et al 2011). These characteristics are present in mats that form on soft agar (Reynolds and Fink 2001) and in complex colony biofilms (sometimes referred to as "fluffy colonies") that are distinguished from nonbiofilm colonies (also described as simple or smooth colonies) by intricate, organized, and strain-specific architecture (Supporting Information, Figure S1) (Palková and Váchová 2006;Granek and Magwene 2010;Honigberg 2011).…”
mentioning
confidence: 99%
“…Using x-ray computed tomography, they have shown that this biofilm can also be impenetrable to gas. In another study, Váchová et al [71] showed that wild yeast biofilms can develop drug resistance "in which specialized cells jointly execute multiple protection strategies." In particular, their analysis shows that the cells selectively create permeable EPS, while coordinated efflux pumps actively expel toxic substances outside the cell clusters.…”
Section: Discussionmentioning
confidence: 99%